STUDIES ON CALCIUM AND MAGNESIUM METABOLISM IN DISEASE : II. CALCIUM AND MAGNESIUM METABOLISM IN MULTIPLE CARTILAGINOUS EXOSTOSIS. - Underhill, Frank P. (The Rockefeller University Press, 1920)
In the stabilized stage of exostosis calcium exchange differs little from that of a normal individual whether the abnormal subject is maintained upon a calcium-poor diet or upon one rich in this element. In the progressive stage of the disease calcium metabolism is markedly different from the normal in that calcium is lost from the body in large amounts when the subject is maintained upon a calcium-poor diet. This excessive elimination of calcium is by way of both the urine and feces in a normal ratio. When placed upon a calcium-rich diet calcium is retained to an extent not widely deviating from that obtained in normal subjects. A resumption to a calcium-poor diet again induces excessive calcium elimination. In the stabilized stage of exostosis magnesium excretion is two or three times greater than the intake whether the subject is maintained upon a diet poor or rich in magnesium. In the progressive stage of the disease the general type of magnesium excretion resembles that of the stabilized stage but the degree of elimination is not so marked. Magnesium added to the diet in the stabilized stage is promptly excreted. The same test applied to the progressive stage gives evidence of retention of some magnesium. The degree of retention, however, is much less than that shown by normal individuals. Absorption of both calcium and magnesium in exostosis is not inferior to that of normal subjects. The facts enumerated suggest that in the early stages of exostosis, that is during the proliferative cartilage changes, the progress of the disease may perhaps be checked by proper dietary procedure — restriction of calcium and magnesium intake.